Earthworm populations under six weed control strategies in a banana plantation. - Agüero-Alvarado, Renán; Rojas, Silvia; Pérez, Leonardo (Agronomía Mesoamericana, 2006)
Six weed management strategies were established in with banana plantation; in San Pablo, a farm located in the Atlantic region of Costa Rica. Since then, earthworm counts have been performed at regular intervals. Weed management strategies consisted of: 1- unweeded control. 2- Hand weeded control at monthly intervals. 3- Glyphosate (Ranger Plus-680 g/kg; at 0.687% w/v) applications at eight week intervals. 4- Paraquat (Gramoxone-200 g/l, at 0.75% v/v) at monthly intervals. 5- Glufosinate (Finale-150 g/l, at 1% v/v) applications at eight week intervals. 6- Monitored treatment, depending on detected weeds, only in the area of maximum weed-crop interference. Earthworms were counted, at each sampling time, from four 15625 cm3 soil samples of each plot. Samples were taken from different microhabitats, including soil covered with Paspalum conjugatum; soil covered with Panicum zizanoides; soil covered with banana residues (leaves, pseudo-stems) and bare soil. Soil samples from sites covered with banana residues or Paspalum conjugatum showed the highest earthworm counts, followed by soil covered with Panicum zizanoides and bare soil. A direct effect of weed management strategies on earthworm number has not been detected.